Checklist and comments on the jumping plant-lice (Hemiptera: Psylloidea) from the Indian subcontinent - Burckhardt, Daniel; Sharma, Anamika; Raman, Anantanarayanan (Zootaxa, 2018)
A checklist comprising information on taxonomy, distribution and host plants is provided for 161 species of jumping plant-lice from the Indian subcontinent (Bangladesh, Bhutan, India, Pakistan, Sri Lanka) based on published records and museum material. In addition there are 15 species recorded in the literature which are identified to genus only. Museum material provides eight new country and two new state (within India) records. The taxonomy is updated and following nomenclatorial acts are proposed: new genus (1), new generic synonymies (2), designation of type species (1), new species synonymies (5), replacement names for primary homonyms at species level (3), new status of subspecies (3), new combinations (23). Toonapsylla Burckhardt, gen. nov. is described for Psylla cedrelae (Kieffer, 1905). The new genus belongs to Mastigimatinae (Calophyidae) and is probably closest related to Bharatiana and Mastigimas, both associated with Cedrela and Toona (Meliaceae). The new genus is diagnosed and a key is provided for the world genera of Mastigimatinae. The Neoptropical genus Allophorina Hodkinson is transferred here from Mastigimatinae (Calophyidae) to Psyllinae (Psyllidae).